(untitled) (Journal of Pathology of Nepal, 2024)
Background: Thrombocytopenia by definition signifies a platelet count below 1,50,000/mm3 but this does not reflect the underlying pathology. Management of these patients significantly depends on identifying the primary cause of thrombocytopenia. With advances in automation, analyzers can now measure platelet parameters like mean platelet volume, Platelet distribution width, and Platelet large cell ratio which are potential biomarkers of platelet morphology. Presently, these non-invasive and cost-efficient diagnostic markers are quite underused. The study aimed to understand the relationship of instrument-derived platelet parameters with respect to the categorizing of thrombocytopenia based on underlying pathophysiology. Materials and methods: A prospective study was conducted from September 2018 to October 2020consisting of 315 cases of hyperdestructive thrombocytopenia and 54 cases of hypoproductive thrombocytopenia. After collecting the important clinical details, platelet count along with instrument-derived platelet indices was noted. A comparison of platelet indices was done between the two groups. Results: In the hyper-destructive group, the mean platelet indices were found to be significantly higher in comparison to the hypo-productive group. No significant correlation was obtained between the platelet count severity and various platelet indices. Mean platelet volume had the highest sensitivity and specificity in differentiating hyper-destructive thrombocytopenia from the hypo-productive group. Conclusions: Platelet indices aid in distinguishing hyper-destructive from hypo-productive causes of thrombocytopenia. Of the three indices analyzed, Mean platelet volume was shown to be a better parameter in differentiating the two groups.